Keanekaragaman Jenis Kantung Semar (Nepenthes spp.) di Kawasan Suaka Margasatwa Siranggas Kabupaten Pakpak Bharat - Maidita Fitri br Purba; Yunasfi Yunasfi; Pindi Patana (Peronema Forestry Science Journal, 2015)
Pitcher plant (Nepenthes spp.) is one of the unique carnivorous plant species, the numbers continue to decline in the wild. Habitat destruction caused by human activities and un cultivated exploitation as an ornamental plant threatened its existence. This study aims to invent and determine species diversity of Pitcher plant (Nepenthes spp.) in the area of Siranggas Wildlife Reserve . The study was conducted at a height categories: 900 – 1.000 meter above see level (m asl) (found 6 types Nepenthes Nepenthes grasilis; Nepenthes mirabilis; Nepenthes tobaica; Nepenthes sp.1 ; Nepenthes sp. 2; and Nepenthes sp. 3),  1.100- 1.200 m asl (none of Nepenthes) and 1.200 – 1.300 m asl (found 3 types of  Nepenthes; Nepenthes reindwardtiana, Nepenthes rhombicaulis and Nepenthes tobaica). Observation ware conducted on three different lines in each height category. Observation path length was 100 m. Determination of the first track was done with purposive sampling method, the next track was determined by systematic sampling. Observation of Nepenthes spp. used of sampling plots 20 m x 20 m. Nepenthes spp. found 8 types of Nepenthes grasilis, Nepenthes mirabilis, Nepenthes reinwardtiana, Nepenthes rhombicaulis, Nepenthes tobaica, and 3 types were unknown (sp.1, sp.2, sp.3).Keywords: Nepenthes spp., Siranggas Wildlife Reserve, Exploitation.